2020
DOI: 10.1111/joor.13026
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and findings of fibre‐optic endoscopic evaluation of swallowing in hospitalised patients with dysphagia

Abstract: Swallowing disorder or dysphagia is quite common in hospitalised patients. Using fibre‐optic endoscopic evaluation of swallowing (FEES) is one of the clinical standards for evaluating swallowing disorder to prevent serious consequences such as aspiration pneumonia. This study aimed to determine the prevalence and the associated risk of dysphagia in hospitalised patients by using FEES finding. We retrospectively analysed the FEES records from the patients who were screened and suspected of swallowing problems b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Dysphagia is a frequent complaint of patients presenting in GI clinics [7][8][9][10]. The causes of dysphagia of esophageal origin that are identified commonly are benign and malignant strictures of esophagus, reflux esophagitis, Schatzki's ring, compression occurring externally from a malignancy, disorders of motility, scleroderma and achalasia [11][12][13][14][15][16]. In some population-based studies, the rates of prevalence of dysphagia have been reported to be 17-25% with a peak in symptoms at the age of 40-49 years for both gender [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is a frequent complaint of patients presenting in GI clinics [7][8][9][10]. The causes of dysphagia of esophageal origin that are identified commonly are benign and malignant strictures of esophagus, reflux esophagitis, Schatzki's ring, compression occurring externally from a malignancy, disorders of motility, scleroderma and achalasia [11][12][13][14][15][16]. In some population-based studies, the rates of prevalence of dysphagia have been reported to be 17-25% with a peak in symptoms at the age of 40-49 years for both gender [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the availability of valid reporting tools, there is a lack of use of standardized secretion ratings in existing literature. Many recent studies assess secretions as a dichotomous variable, or use their own choice of categorization, which primarily focus on the location/depth of secretion pooling [7,8 ▪ ,9,19 ▪ ,20,22,26,27]. A number of recently published intervention studies have assessed secretion severity as a primary or secondary outcome measure to determine responses to therapeutic interventions [26,28]; however, only one used a validated tool [28].…”
Section: Research Use Of Secretion Toolsmentioning
confidence: 99%
“…The predictive value of accumulated secretions for swallow impairment and health outcomes is well established and continues to receive attention in recent publications [7,8 ▪ ,9,10,20]. Yet, understanding of its underlying mechanisms is limited.…”
Section: Pathophysiology Associated With Accumulated Secretionsmentioning
confidence: 99%
See 2 more Smart Citations